PENGARUH COOPERATIVE LEARNING TIPE JIGSAW TERHADAP HARGA DIRI (SELF ESTEEM) MAHASISWA - Riza Yulina Amry; Aris Setyawan (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: The conventional teaching phenomenon in teaching and learning process resulted in students being less active in the learning process. Innovative learning models should be applied so that interpersonal relationships between students, cooperative skills, and student self-confidence can be developed. Cooperative Learning Jigsaw type is one of the innovative learning methods that involve students in the learning process. There are five fundamental elements of cooperative jigsaw learning that can improve students' interpersonal skills, motivation and self-esteem. Objective: To know the influence of cooperative learning method of learning to self esteem of Stikes Surya Global Yogyakarta students.Methods: The research method used in this research is quantitative research with quasy experimental design, and pretest-posttest approach with control group. The sample of this research is second year student of STIKES Surya Global. The insrument used to measure students' self-esteem is the Rosenberg Self Esteem Scale, which consists of 10 items of questions. Then the results are analyzed using the Mann-Whitney test with a value of α 0.05.Results: The results showed that there were significant differences between the intervention group and the control group after intervention learning cooperative learning method with P value 0.000 for the self-esteem variable Conclusion: There is influence of applying cooperative learning jigsaw method toward self study result of student of S1 Study Program of Nursing STIKes Surya Global Yogyakarta